Transcendence, faith and poetry: towards an ontology of the Spirit - Keeling, Michael (Theology, 2024)
Our current understanding of the evolution of the cosmos and the place in it of Homo sapiens requires a reassessment of transcendence and in particular of the Christian faith and the importance of the Spirit of God, leading to a revised view of theology as being primarily a form of poetry about human experience of transcendence, open to ambiguity, contradiction and imagination, rather than credal certainty.